P15 Aortitis requiring cardiothoracic surgery in a case of secondary syphilis. (18th May 2015) - Newton, Pippa; Saxon, Cara; Ahmad, Sameena
Abstract : Background/introduction: Cardiac complications of syphilis typically occur 10–30 years after being infected. There has been a recent case of aortitis in secondary syphilis in the literature. Aim(s)/objectives: To report a case of syphilitic aortitis in a patient recently infected with syphilis. Methods: Case report. Results: A 37-year-old white British female was found wandering the streets semi-clothed by paramedics. Background: bipolar/schizoaffective disorder with previous psychosis and known substance misuse. A loud early diastolic murmur was found on examination. An ECG revealed anterior T wave changes. Troponin was >2000 ng/L and echocardiogram (ECHO) revealed a dilated left ventricle with severe aortic regurgitation (AR). Transoesophageal ECHO demonstrated an oedematous, thickened aortic root. CT aortogram confirmed aortitis. Syphilis serology was positive (RPR 1:256). She had a male partner of 5 years and had never had a syphilis test before. Due to penicillin allergy she was commenced on Doxycycline for 28 days with adjuvent. Three weeks into treatment she developed heart failure and was admitted to intensive care. ECHO revealed an ejection fraction of 30% and progressive valvular pathology. Following desensitisation she commenced on benzylpenicillin plus probenacid for 17 days. Two weeks into treatment she underwent an aortic valve replacement and coronary artery bypass graft (x2). After a protracted recovery she was discharged two months later and remains under cardiology follow up. Discussion/conclusion: Whilst it is not exactly clear when this patient acquired syphilis the high RPR titres suggest that infection was recent. This case demonstrates a rare but serious and life-threatening complication of early syphilis.